Living a Good Way of Life: Perspectives from American Indian and First Nation Young Adults. Issue 1 (4th September 2019) - Kading, Margarette L.; Gonzalez, Miigis B.; Herman, Kaley A.; Gonzalez, John; Walls, Melissa L.
Abstract: In this study, we respond to calls for strengths‐based Indigenous research by highlighting American Indian and First Nations (Anishinaabe) perspectives on wellness. We engaged with Anishinaabe community members by using an iterative, collaborative Group Concept Mapping methodology to define strengths from a within‐culture lens. Participants ( n  = 13) shared what it means to live a good way of life/have wellness for Anishinaabe young adults, ranked/sorted their ideas, and shared their understanding of the map. Results were represented by nine clusters of wellness, which addressed aspects of self‐care, self‐determination, actualization, community connectedness, traditional knowledge, responsibility to family, compassionate respect toward others, enculturation, and connectedness with earth/ancestors. The clusters were interrelated, primarily in the relationship between self‐care and focus on others. The results are interpreted by the authors and Anishinaabe community members though the use of the Seven Grandfather Teachings, which provide a framework for understanding Anishinaabe wellness. The Seven Grandfather Teachings include Honesty (Gwayakwaadiziwin), Respect (Manaadendamowin), Humility (Dabaadendiziwin), Love (Zaagi'idiwin), Wisdom (Nibwaakaawin), Bravery/Courage (Aakode'ewin), and Truth (Debwewin). Highlights: Group Concept Mapping was used to define wellness from a within‐culture, detailed vantage point. Anishinaabe young adults shared what it means to live a good way of life/have wellness. The Seven Grandfather Teachings provide a framework for understanding Anishinaabe wellness. Community collaborators contributed substantively to the analysis and interpretation of results.